Management of diabetes mellitus in people living with HIV: A single-center experience - Cattaneo, Dario; Gidaro, Antonio; Rossi, Antonio; Merlo, Andrea; Formenti, Tiziana; Meraviglia, Paola; Antinori, Spinello; Gervasoni, Cristina (Frontiers in Pharmacology, 2023)
Background: Diabetes mellitus (DM) is more common in people living with HIV (PLWH) than in HIV-negative patients. Here we aimed to describe the response of PLWH with DM to glucose-lowering therapies in a reference hospital of northern Italy. Setting: 200 PLWH and DM were identified from the database of our clinic. Methods: Good control of DM was defined as having fasting glucose <130 mg/dl or HbA1c < 53 mmol/mol. The distribution of glucose-lowering therapies in PLWH was compared with that of HIV-negative patients with DM. Results: Mean total fasting glucose and HbA1C were 143 ± 50 mg/dl (51% exceeding the 130 mg/dl cutoff) and 51 ± 16 mmol/mol (30% exceeding the 53 mmol/mol cutoff), respectively. PLWH were less treated with dipeptidyl peptidase-4 inhibitors (1.7% versus 9.6%, p < 0.01) and sulfonylureas (3.3% versus 13.2%, p < 0.01), being conversely more frequently treated with metformin (53.8% versus 37.7%, p < 0.01), glifozins plus metformin (7.1% versus 2.0%, p < 0.05) or insulin plus other glucose-lowering agents (5.5% versus 0.5%, p < 0.01). Conclusion: An underuse of dipeptidyl peptidase-4 inhibitors was found which was, however, counterbalanced by a higher use of combination of drugs (including glifozins). A rational assessment of drug-drug interactions would contribute to a better selection of the best glucose lowering agent for each antiretroviral therapy.